Happy in the Hood? The Impact of Residential Segregation on Self-Reported Happiness - Chris M. Herbst; Joanna Lucio (Institute for the Study of Labor (IZA), 2014)
Previous research consistently finds that racially-based residential segregation is associated with poor economic, health, and social outcomes. The purpose of this paper is to explore the relationship between residential segregation and self-reported happiness. Using panel data from the National Survey of Families and Households (NSFH), we begin by estimating ordinary least squares (OLS) regressions of happiness on a measure of MSA-level segregation, controlling for a rich set of individual, neighborhood, and state characteristics. The OLS results suggest that increased segregation is associated with a reduction in happiness among blacks. To deal more appropriately with the potential endogeneity of location choice, we extend the methodology to fully exploit the panel structure of the NSFH and incorporate individual fixed effects into the happiness equation. Contrary to the OLS results, our fixed effects estimates imply that blacks are happier in more segregated metropolitan areas. The paper discusses the implications of these results within the context of current integration policies.
Keywords: J10; 330; happiness; residential segregation; neighborhood preferences